Implementing a laterite soil-peat-rice husk soil mixture to assess the performance of heavy metal migration - Maheera Mohamad; Khai Lin Chong; Salmah Omar; Md. Abdul Kafi; Nabilah Mohamad Khairi; Siti Nor Farhana Zakaria; Vignes Chellamuthu (John Wiley and Sons Inc., 2024)
Solid waste can be effectively managed through disposal in engineered landfills, which are specifically designed facilities. The application of daily soil cover at these landfills is vital for mitigating leachate generation and protecting groundwater from contamination. This study aims to investigate whether a mixture of laterite soil (LS), peat soil (PS), and rice husk (RH) can reduce the migration of heavy metals within a landfill setting. Heavy metal pollution poses a significant environmental challenge in Malaysia, specifically the five metals focused on in this research: Cd, Cr, Cu, Ni, and Zn. The study evaluates the adsorption capacity of the soil mixture for these metal ions by utilizing laboratory analyses of key parameters such as pH and cation exchange capacity (CEC). To assess the effectiveness of the soil mixture, various combinations were tested, highlighting a blend of 50% LS, 40% PS, and 10% RH as the most effective. An equilibrium study was conducted, wherein metal ion solutions were prepared, allowing the soil mixtures to interact with these solutions until a state of equilibrium was achieved. Subsequently, batch adsorption experiments were performed to measure the mixtures’ ability to adsorb the metal ions, with ongoing assessment of pH and CEC. The results indicate that the selected mixture can significantly reduce metal ion concentrations, demonstrating its potential as a viable daily cover for landfills. Ultimately, this research provides valuable insights into strategies for minimizing heavy metal migration in landfills and safeguarding groundwater resources.